ЭЛЕКТРОМАГНИТ ЭЛАСТИК ЮПҚА АНИЗОТРОП ПЛАСТИНАЛАРИНИНГ ТЕБРАНИШИ МАСАЛАСИНИНГ МАТЕМАТИК МОДЕЛИНИ ИШЛАБ ЧИҚИШ - Артикбаев, М.А. (SCIENCE and SOCIETY, 2021)
The article is devoted to the mathematical modeling of the electromagnetic-elastic deformation-stress state of anisotropic plates of thin complex shape.
Keywords: electromagnetic-elastic; anisotropic plate; Hamilton-Ostrogradsky variational principle; Kirchhoff-Lyav hypothesis; Cauchy relations; Hooke's law; Maxwell's electromagnetic tensor